2017
DOI: 10.1088/1361-6560/aa6ce2
|View full text |Cite
|
Sign up to set email alerts
|

A gas scintillator detector for 2D dose profile monitoring in pencil beam scanning and pulsed beam proton radiotherapy treatments

Abstract: In order to address dosimetry demands during proton therapy treatments utilizing pencil beam scanning and/or pulsed beam accelerators, we have developed a xenon-filled Gas Scintillation Detector (GSD) that can monitor delivered dose and two-dimensional beam centroid position pulse-by-pulse in real time, with high response linearity up to high instantaneous dose rates. We present design considerations for the GSD and results of beam tests carried out at operating proton therapy clinics. In addition to demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Novel approaches based on gas scintillators are a promising alternative for beam monitoring at UHDRs, thanks to the high level of transparency and fast response. A xenon gas scintillator coupled to large photomultiplier tubes (PMTs) for real-time 2D beam monitoring for pulsed and pencil beam scanning proton RT treatments was used by Vigdor et al 103 A spatial resolution of a few hundred micrometers was achieved, with a linear response within 1% up to a dose rate of 300 Gy/s. An alternative approach was investigated using air as a medium in which fluorescence is developed.…”
Section: Radioluminescence and Cherenkov Radiation Dosimetrymentioning
confidence: 99%
“…Novel approaches based on gas scintillators are a promising alternative for beam monitoring at UHDRs, thanks to the high level of transparency and fast response. A xenon gas scintillator coupled to large photomultiplier tubes (PMTs) for real-time 2D beam monitoring for pulsed and pencil beam scanning proton RT treatments was used by Vigdor et al 103 A spatial resolution of a few hundred micrometers was achieved, with a linear response within 1% up to a dose rate of 300 Gy/s. An alternative approach was investigated using air as a medium in which fluorescence is developed.…”
Section: Radioluminescence and Cherenkov Radiation Dosimetrymentioning
confidence: 99%
“…29 Two-and three-dimensional measurements with luminescent technology have also been successfully implemented. [30][31][32][33][34]…”
Section: Measuring Physical Beam Parametersmentioning
confidence: 99%
“…recently demonstrated the successful implementation of a 100.33emμm$\ {{\mu {\text m}}}$ thick BC‐400 film plastic scintillator coupled to a 1 mm diameter optical fiber in a synchrotron X‐ray beam, which showed excellent performance at dose rates of up to 4435 Gy/s 29 . Two‐ and three‐dimensional measurements with luminescent technology have also been successfully implemented 30–34 …”
Section: Flash Terminology and Critical Beam Parametersmentioning
confidence: 99%
“…Due to its high spatio-temporal resolution, optical imaging has also been used for quality assurance purposes in pencil beam scanning (PBS) proton therapy; a technique which also utilizes high dose rates (up to 200 Gy/s near the Bragg Peak). For example, Vigdor et al [97] used a xenon gas scintillator coupled to large PMTs for monitoring 2D beam characteristics in real-time for pulsed and pencil beam scanning proton radiotherapy treatments. The authors demonstrated a spatial resolution of a few hundred microns.…”
Section: Scintillatorsmentioning
confidence: 99%